A Comparison of Pedagogical Practices and Beliefs in International and Domestic Mathematics Teaching Assistants - Kim, Minsu (Journal of International Students, 2014)
International and domestic mathematics teaching assistants (MTAs) are a critical part of mathematics education because they teach a substantial portion of low-level mathematics courses at research institutions. Even if there are several factors to build on MTAs’ pedagogical practices, MTAs’ beliefs significantly influence the MTAs’ practices. The purpose of this study is to explore different beliefs and pedagogical practices between international and domestic MTAs. The findings reveal that there is consistency between the MTAs’ beliefs and their pedagogical practices. In addition, the two groups adopt significantly different approaches of how to teach new concepts, definitions, and problem-solving for students’ conceptual understanding and how to interact with their students. These results contribute to the body of knowledge of MTAs and the adaptation of professional development programs of MTAs. In addition, faculty in mathematics has an opportunity to understand the differences in beliefs and pedagogical practices between IMTAs and DMTAs.